Differential cognitive correlates of tau and neurofilament light chain in cerebrospinal fluid of frontotemporal lobar degeneration patients with and without Alzheimer's markers. (1st February 2022) - Vasilevskaya, Anna; Taghdiri, Foad; Multani, Namita; Salvo, Cristina; Anor, Cassandra Jessica; Misquitta, Karen; Burke, Charles; Tang‐Wai, David F.; Lang, Anthony E.; Fox, Susan; Slow, Elizabeth; Tartaglia, Maria Carmela
Abstract: Background: Frontotemporal lobar degeneration (FTLD) phenotypes can be associated with Alzheimer's disease (AD). It is unknown whether differences exist in relationship between markers of degeneration such as tau and neurofilament light chain (NFL) and cognition between FTLD with and without AD. Method: 40 FTLD patients were included in this study: (A) 31 FTLD without AD [5 behavioral variant FTD, 11 corticobasal syndrome (CBS), 1 non‐fluent variant primary progressive aphasia (nfvPPA), 12 progressive supranuclear palsy (PSP), 2 semantic variant PPA (svPPA); age (67.74±10.28); sex (20M:11F)]; and (B) 9 FTLD positive for AD [6 CBS‐AD, 1 nfvPPA‐AD, 1 PSP‐AD, 1 svPPA‐AD; age (66±8.46); sex (5M:4F)]. CSF levels of Aβ42, phosphorylated tau (p‐tau) & total tau (t‐tau) were measured using sandwich ELISA and AD pathology was deemed present if p‐tau > 68 pg/mL and Aβ42 to t‐tau index < 0.8. CSF NFL was measured using SIMOA. Full neuropsychological battery was completed, controlled for age/education. Result: In the FTLD cohort, significant relationships were observed between CSF t‐tau and CDR sum of boxes (r=0.599, p=.001) and MOCA (r=‐0.530, p=.004). In FTLD group, digit span backwards (DSB) was significantly associated with CSF t‐tau (r=‐0.492, p=.009) & NFL (r=‐0.427, p=.02); while verbal fluency, Trail Making Test part A & digit span forward (DSF) were only related to NFL (r=‐0.410, p=.03; r=0.463, p=.02; r=‐0.374, p=.05, respectively). In the FTLD‐AD cohort, MOCA was significantly associated with CSF p‐tau (r=‐1.00, p<.0001) & t‐tau (r=‐0.887, p=.02); memory and executive function tests including California verbal learning test 30s recall, DSB & DSF were significantly associated with CSF t‐tau (r=‐0.788, p=.04; r=‐0.836, p=.04; r=‐0.760, p=.07, respectively); while verbal fluency & category fluency were significantly associated with CSF markers of NFL (r=‐0.841, p=.04; r=‐1.00, p<.0001), p‐tau (r=‐0.981, p<.001; r=‐1.00, p<.0001), & t‐tau (r=‐0.984, p<.001; r=‐0.977, p=.004). Conclusion: In both FTLD with and without AD, overall severity was related to CSF t‐tau but executive function in FTLD without AD was related to CSF NFL while in FTLD‐AD it was related to p‐tau and t‐tau. The presence of AD in FTLD phenotypes alters relationship to NFL, which may be indicative of differences in extent of degeneration.